Finding consensus on frailty assessment in acute care through Delphi method. Issue 10 (14th October 2016) - Soong, John T Y; Poots, Alan J; Bell, Derek
Abstract : Objective: We seek to address gaps in knowledge and agreement around optimal frailty assessment in the acute medical care setting. Frailty is a common term describing older persons who are at increased risk of developing multimorbidity, disability, institutionalisation and death. Consensus has not been reached on the practical implementation of this concept to assess clinically and manage older persons in the acute care setting. Design: Modified Delphi, via electronic questionnaire. Questions included ranking items that best recognise frailty, optimal timing, location and contextual elements of a successful tool. Intraclass correlation coefficients for overall levels of agreement, with consensus and stability tested by 2-way ANOVA with absolute agreement and Fisher's exact test. Participants: A panel of national experts (academics, front-line clinicians and specialist charities) were invited to electronic correspondence. Results: Variables reflecting accumulated deficit and high resource usage were perceived by participants as the most useful indicators of frailty in the acute care setting. The Acute Medical Unit and Care of the older Persons Ward were perceived as optimum settings for frailty assessment. 'Clinically meaningful and relevant', 'simple (easy to use)' and 'accessible by multidisciplinary team' were perceived as characteristics of a successful frailty assessment tool in the acute care setting. No agreement was reached on optimal timing, number of variables and organisational structures. Conclusions: This study is a first step in developing consensus for a clinically relevant frailty assessment model for the acute care setting, providing content validation and illuminating contextual requirements. Testing on clinical data sets is a research priority.